Uncertain Zero-One Law and Convergence of Uncertain Sequence - Zhiqiang Zhang; Weiqi Liu; Xiumei Chen (Discrete Dynamics in Nature and Society)
This paper is concerned with situations in which the uncertain measure of an event can only be zero or one, and the uncertain zero-one laws are derived within the framework of uncertainty theory that can be seen as the counterpart of Kolmogorov zero-one law and Borel-Cantelli lemma, which can be used as a tool for solving some problems concerning almost sure convergence of uncertain sequence.